The Effect of Problem-Based Learning on the Critical Thinking Skill of the Students - Vegas, Susana Osiana; Djukri, Djukri (SCAD Independent, 2021)
This research aimed to determine the effect of the problem based learning model on critical thinking skills in excretory system subject. The research was quasi experimental research by using pretest postest control group design. The population of this research was all students of SMA Negeri 1 Prambanan. The research sample of this research used two classes, class XII MIPA 4 with 27 students as the control class and class XII MIPA 3 with 31 students as the experimental class implementing problem based learning. Data were collected by using a test instrument in the form of multiple choice questions. The data obtained were analyzed using the Independent sample T-test. The calculation results showed a significant value of 0,000 < 0,05, thus, it can be concluded that there was a difference in the critical thinking skills between the control and experimental class.